Design and ethics reflections on practice - Felton, Emma; Zelenko, Oksana; Vaughan, Suzi (Routledge, 2012)
"This book presents a multi-disciplinary collection of writing with authors reflecting on design as a process in which ethics and social responsibility are paramount. With contributions from fields as diverse architecture, fashion, urban design, philosophy and education, this book presents innovative ways of thinking about and doing design." -- Publisher